HUBUNGAN ANTARA MOTIVASI BERPRESTASI SISWA DAN POLA ASUH ORANG TUA DENGAN PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL KELAS III SD NEGERI SE-GUGUS 3 KECAMATAN PRAMBANAN - Indah Ratnasari; AL Sugijanto (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
This study aimed to describe (1) correlation between learning motivation with learning achievement of social science subject, (2) correlation between parents’ parenting with learning achievement of social science subject, (3) correlation between learning motivation and parents’ parenting with learning achievement of social science subject among the third grade students of state elementary school in Prambanan District. The type of this study was ex-post facto. Data collecting techniques used questionnaire and documentation. Data analyzing techniques used descriptive technique and hypothesis testing by using double regression with two predictors that was started by independence test, normality test, and linearity test. This study shows that the correlation coefficient of each independent variable has a positive correlation with dependent variable. The score of = 0.24585 > rtable 0.18588, it means that learning motivation has a positive and significant correlation with learning achievement of social science subject. The score of = 0.23821 > rtable 0.18588, it means that parents’ parenting has a positive and significant correlation with learning achievement of social science subject. The study shows that there is a positive and significant correlation between learning motivation and parents’ parenting with learning achievement of social subject (R= 0.32811 and Freg = 6,575 > Ftable = 3.0828). The score of R2 is 0.10766, it means that learning motivation and parents’ parenting gives contribution 10.766% toward learning achievement of social science subject, while 89.234% was influenced by other factors that were not entered in regression model. Learning motivation gave effective contribution 5.59648% toward learning achievement of social science subject and parents’ parenting gives contribution 5.19646% toward learning achievement of social science subject.